(untitled) (Journal of Fiber Bioengineering and Informatics, 2025)
To increase the protective capacity of yarns while maintaining human wearing comfort, pure UHMWPE filament and Spandex were combined to fabricate an elastic high-performance covered yarn. The various wrapping process parameters were adjusted to prepare this single-lay-covered yarn with a perfect wrapping status, which also can achieve the balance of strength and elasticity. It was discovered that the wrapping process seriously affected the covered yarn’s performance, and the new single-lay covered yarn showed desirable high strength and super elasticity. The strength of covered yarns shows three types of trend with the twist added, including first steep (300 t/m∼400 t/m), then gentle (500 t/m∼600 t/m) and last drastic (700 t/m∼800 t/m). The covered yarn twisted at 700 t/m shows the optimal coverage morphology, excellent elasticity, and high strength. Finally, an elastic cut-resistant fabric is practically knitted by this fabricated elastic cut-resistant composite yarn, and it presents good flexibility and protection with Level 2 cut resistance under standard testing. The fabricated elastic high-performance covered yarn is an ideal material for producing highly elastic protective textiles and is applied to manufacture high-quality flexible protective equipment.